Bioinseticidas e suas nanoformulações para o controle da mosca- negras-dos-citros Aleurocanthus woglumi : alternativa de manejo integrado na agricultura moderna - Santana, Emile Dayara Rabelo (2020)
Citriculture is one of the main agricultural activities throughout the world but its production has been threatened due to the attack of the citrus blackfly (Aleurocanthus woglumi). This insect causes direct and indirect damage to plants, causing physiological changes and consequent reduction in fruit production. Its control is based on organosynthetic insecticides, although its indiscriminate use has caused adverse effects on society and the environment. As a result, essential oils rose as an alternative. However, despite the toxicity on agricultural pests, some of its characteristics make its use in the fields unfeasible. Consequentely, nanoformulations have been studied in the agricultural field. Nanotechnology allows th bioactivity of the essential oil maintenance while increasing its application efficiency. Therefore, in this study, we evaluated the effects of the Lippia sidoides essential oil, its major compound thymol, their nanoformulations, the espinetoram insecticide and imidacloprid on A. woglumi, in addition to the phytotoxicity of the treatments. In order to do so, toxicity bioassays were carried out on eggs and adults, in addition to repellency / deterrence and anti- oviposition bioassays. A total of nine compounds were found in the L. sidoides essential oil, with thymol being the major compound (73.23%). Nanoformulations presented nanometric particle size (10 to 100 nm) and spherical shape. Through the contact exposure route, thymol (CL50 = 0.8922 mg ml-1) and the essential oil (CL50 = 3.996 mg ml-1) were the most toxic compounds. The opposite was observed by fumigation, in which oil was the most toxic compound (CL50 = 2,715 μl L-1) followed by thymol (CL50 = 5.033 μl L-1). The contact nanoformulations presented CL50 of 39.68 mg ml-1 and 55.11 mg ml-1. By Fumigation, the LC50 were 9.074 and 54.04 μl L-1 , for thymol and oil, respectively. Bioinsecticides acted quickly on adults of A. woglumi, causing 50% mortality in less than 3 hours. The nanoformulation of thymol caused the greatest ovicidal effect, causing no phytotoxicity to the plant. As for repellency and anti-oviposition, bioinsecticides decreased the amount of adults and eggs on treated leaves. Based on the results obtained, the bioinsecticides tested demonstrated high toxicity on the blackfly with superior results to the current active ingredient used for its control. Therefore, they consist of potential alternative molecules for the integrated management of this pest.